2020
DOI: 10.35654/ijnhs.v3i6.368
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Acupressure and Smart Gymnastic on Fasting Blood Sugar Levels among Patients with Type II Diabetes Mellitus

Abstract: Diabetes mellitus (DM) is a glucose metabolism disease characterized by an increase in blood sugar levels and impaired metabolism of fats, protein, and carbohydrates due to a lack of the hormone insulin, both absolutely and relatively. Alternative treatment of diabetes mellitus with complementary therapies, namely acupressure and smart gymnastic, can improve the fasting blood sugar level. This study aims to determine the effectiveness of acupressure and smart gymnastic on fasting blood sugar levels among patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The pancreas gland was produced by massage in this point, so the hormones insulin and glucagon, will keep balance blood sugar levels. 16 This study same with Suyanto, that showed better-increased foot sensation after combining diabetic foot exercise and spa than diabetic foot exercises only. 17 Diabetic foot exercise improves foot sensation, so it reduces the risk of injury in individuals with Type 2 Diabetes Mellitus (T2DM).…”
Section: Original Articlesupporting
confidence: 60%
“…The pancreas gland was produced by massage in this point, so the hormones insulin and glucagon, will keep balance blood sugar levels. 16 This study same with Suyanto, that showed better-increased foot sensation after combining diabetic foot exercise and spa than diabetic foot exercises only. 17 Diabetic foot exercise improves foot sensation, so it reduces the risk of injury in individuals with Type 2 Diabetes Mellitus (T2DM).…”
Section: Original Articlesupporting
confidence: 60%
“…Albumin topical preparations can be absorbed by the body through transmucosal delivery. Albumin functions in regulating blood osmotic pressure and maintaining water content in blood plasma during the inflammatory phase, therefore, helps to form body tissues in surgical wounds, accelerates tissue healing, and carries away nutrients and oxygen for the formation of new tissue in the proliferative phase (29). Albumin contains natural proteins and collagen that compile the extracellular matrix which induces growth factors, cell migration and adhesion, and tissue regeneration (5).…”
Section: Discussionmentioning
confidence: 99%
“…This condition inhibits the adrenal cortex from releasing the hormone cortisol. This decrease in the hormone cortisol inhibits gluconeogenesis and increases glucose use by body cells (Anaabawati et al, 2021;Janah & Prajayanti, 2023;Sherwood, 2014).…”
Section: Discussionmentioning
confidence: 99%